The Role of LC-MS in Profiling Bioactive Compounds from Plant Waste for Cosmetic Applications: A General Overview - Gilda D’Urso; Alessandra Capuano; Francesca Fantasma; Maria Giovanna Chini; Vincenzo De Felice; Gabriella Saviano; Gianluigi Lauro; Agostino Casapullo; Giuseppe Bifulco; Maria Iorizzi (Plants)
The agro-industrial sector produces large amounts of by-products that have a high environmental impact, so it has become essential to recover food waste at all levels. This is because it often contains bioactive molecules that can be a valuable source of new products such as animal feed, biopolymers, or products for human use, (e.g., cosmetics and nutraceuticals) due to its antioxidant, antimicrobial, and anti-inflammatory properties. Advanced analytical methodologies such as liquid chromatography coupled to mass spectrometry (LC-MS) are crucial for the characterisation of bioactive chemicals in these waste materials. LC-MS enables both targeted and untargeted metabolomic approaches, facilitating the identification and quantification of a wide range of secondary metabolites, including polyphenols, flavonoids, alkaloids, and terpenoids. The choice of extraction methodology is essential for the precise identification and quantification of these metabolites. This study provides an overview of LC-MS as an effective tool for analysing complex extracts derived from plant waste, discussing both methodological aspects and typical bioactive metabolites identified, and offering examples of their potential applications in cosmeceutics.